Strategic ICT Leadership in Constrained Environments: GITO Agency in South Africa’s Public Sector – Insights for Developing Nations - Mr. Ashley Latchu; Mr. Shawren Singh (Researchers World - International Refereed Social Sciences Journal, 2025)
Purpose: This article examines how Government Information Technology Officers (GITOs) in South Africa’s public sector navigate leadership strategically amidst persistent institutional inflexibility, bureaucratic slowdowns, and tight budgets. Despite the good intentions behind formal ICT governance frameworks—like the Corporate Governance of ICT Policy Framework, the Public Finance Management Act, and the SITA Act, all designed for accountability and efficiency—actual real-world data tells a different story. The research involved 55 GITOs who worked at national, provincial and local government levels and found that current organizational structures hinder both agility and innovation in the ICT sector. Our research lays bare how GITOs exhibit remarkable adaptive agency, a truth illuminated by looking through lenses like strategic leadership, street-level bureaucracy, and institutional work. These GITOs are far from just carrying out orders; they’re actively working through and around existing regulations. They achieve this through their ability to manipulate situations by forming strategic alliances and negotiating the compliance terms.. This article contributes to ICT governance and public administration literature by foregrounding the lived practices of digital leadership in the Global South and calls for more context-sensitive, flexible governance models that recognise discretion, adaptation, and influence as essential features of public sector ICT leadership.